BI-LIPSCHITZ CONTACT INVARIANCE OF RANK - Nguyen, Xuan Viet Nhan (Trường Đại học Đà Lạt, 2023)
We address the question of whether the Thom-Boardman symbol of a map germ is an invariant with respect to bi-Lipschitz right equivalence. We give a counterexample showing that in general the answer is negative. We prove that the rank of a map germ is a bi-Lipschitz contact invariant. Consequently, the first Thom-Boardman symbol and its length are bi-Lipschitz contact invariants.